Understanding diversity: how university administrators and first-generation non-majority students experience diversity at their university - Blue, James P., author; Gilley, Jerry W., advisor (Colorado State University. Libraries, 2008)
This qualitative study examined how university administrators and first-generation non-majority students experience diversity at their university. The phenomenon of is this a real true picture of New Hope University was examined through data collected in personal and telephone interviews with five college admission officials and six first-generation non-majority freshman students from one university. Themes emerging from the study were Attraction, Codification, Implementation, and Diversity. The theme Attraction expresses the positive words and experiences that solidify the participants' desire and willingness to attend New Hope University (NHU). Supporting themes are presented that clarify the participants' excitement, anxiety, and openness to attend NHU. Codification is a theme that explains the systematic use of their university's strategic plans, admission standards, and policies that administrators are expected to follow in order to achieve the diversity goals of their institution. Supporting themes are presented that indicate a connection between the accomplishment of achieving the institution's diversity goals, while adhering to the strategic plan, admission standards, and policies of the institution. The theme Implementation illustrates the institution's strategies to attract first-generation non-majority freshman students to its campus. Supporting themes will show that these strategies work. The final theme Diversity describes throughout this dissertation the importance and relevance it has to achieving a diverse student body. Its supporting themes will show the impact and importance that diversity has on students making the decision to attend this institution. The findings were interpreted and presented in relationship to the literature.
Keywords: administrators; diversity; first-generation; first-generation students; non-majority; nonmajority; educational sociology; school administration; higher education; multiculturalism and pluralism; college students; colleges and universities; educational administration